2003
DOI: 10.1081/ncn-120026399
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3′-Deoxy-3′-[4-(pyrimidin-1-yl)methyl-1,2,3-triazol-1-yl]thymidine via 1,3-Dipolar Cycloaddition

Abstract: The synthesis of new 3'-deoxy-3'-[4-(pyrimidin-1-yl)methyl-1,2,3-triazol-1-yl]-thymidine 6a-f, from 3'-azido-3'-deoxy-5'-O-monomethoxytrityl-thymidine is described. The key step is the 1,3-dipolar cycloaddition between the azido group of the protected AZT 3 and N-1-propargylpyrimidine derivatives 2a-f. All new derivatives 6a-f were evaluated for their inhibitory effects against the replication of HIV-1 (IIIB), HIV-2 (ROD). No marked activity was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
(17 reference statements)
0
5
1
Order By: Relevance
“…On the other hand, the sterically less-hindered isomer tends to be the major one. 28 But in our hand, it is noticeable that even without copper only the 1,4-triazole isomer was obtained. This was confirmed by an NMR HMBC experiment (Scheme 2) showing a correlation peak between the anomeric proton (δ = 5.69 ppm) and the carbon (proved to be the tertiary carbon by DEPT 135) at the fifth position in the triazole moiety (δ = 133.7 ppm).…”
Section: ■ Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, the sterically less-hindered isomer tends to be the major one. 28 But in our hand, it is noticeable that even without copper only the 1,4-triazole isomer was obtained. This was confirmed by an NMR HMBC experiment (Scheme 2) showing a correlation peak between the anomeric proton (δ = 5.69 ppm) and the carbon (proved to be the tertiary carbon by DEPT 135) at the fifth position in the triazole moiety (δ = 133.7 ppm).…”
Section: ■ Introductionmentioning
confidence: 59%
“…The literature clearly shows that the outcome of the addition of azides to unsymmetrical acetylenes without the addition of any copper catalyst is determined by steric and electronic factors. 28 Such an addition tends to give mainly the isomers with electron-withdrawing groups at the fourth position. On the other hand, the sterically less-hindered isomer tends to be the major one.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A review of acyclonucleosides appeared recently [16]. In connection with our synthetic approaches on the synthesis of acyclic N-and C-nucleosides [17][18][19][20] and the 1,2,3-triazoles [21] and their carbamate analogues [22], we herein report on the synthesis of novel acyclic 1,2,3-triazole Nthionucleoside analogues bearing 1,2,3-triazole ring carrying potential halomethyl and carbamate groups in addition to their rearrangement to the C-thio acyclic analogues via the sulfur participation, as promising antiviral or antineoplastic agents. A few halomethyl nucleoside derivatives have been described with potential cytostatic activity [23,24], such as N-glycosyl(halomethyl)-1,2,3-triazoles [25] and 3-substituted-thymidine analogues [26] as alkylating and antiviral agents, respectively.…”
Section: Acv (Acyclovir Zoviraxmentioning
confidence: 99%
“…[13] This has led to growing use of triazoles for drug discovery. In the field of nucleoside and nucleotide chemistry, HuisgenSharpless cycloaddition has been used as powerful linking reaction to obtain a variety of bioconjugates, [14] modified bases, [15] sugar residues [16] and altered phosphodiester backbones. [17] Here we have applied this approach to the synthesis of aminoacyl-tRNA analogues C and C' and have shown that these compounds inhibit the FemX Wv cell wall target.…”
Section: Introductionmentioning
confidence: 99%